PELAKSANAAN PERATURAN DAERAH KABUPATEN SUKOHARJO NOMOR 13 TAHUN 2011 TENTANG RETRIBUSI DAERAH DALAM PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN SUKOHARJO - Retno Saraswati, Indra Setiawan, Noor Raharjo, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Regional retribution is one type of retribution that is able to give large donation to the increase income of region so as to increase local revenue Sukoharjo. The district government of Sukoharjo has comprehensively regulate of types and object retribution of region into one package arrangements, the Local Regulation Number 13, 2011 about Regional Retribution which these regulations are properly implemented in accordance with applicable regulations. The factors that support the successful implementation of the regional regulation is a factor of the economic growth, the implementation of the law itself, and fare of rates retribution which are still affordable by compulsory retribution. The factors inhibiting the implementation of the law is low public awareness, administrative factors that are inconsistent with reality, a very light penalty factor, service factor and reciprocity provided by the apparatus is not worth the fees to be paid, the retribution objects reduced and the presence of third-party intervention in the management of objects retribution.